The biological relevance of the FspTF transcription factor, homologous of Bqt4, in Fusarium sp. associated with the ambrosia beetle Xylosandrus morigerus - Carreras-Villaseñor, Nohemí; Martínez-Rodríguez, Luis A.; Ibarra-Laclette, Enrique; Monribot-Villanueva, Juan L.; Rodríguez-Haas, Benjamín; Guerrero-Analco, José A.; Sánchez-Rangel, Diana (Frontiers in Microbiology, 2023)
Transcription factors in phytopathogenic fungi are key players due to their gene expression regulation leading to fungal growth and pathogenicity. The KilA-N family encompass transcription factors unique to fungi, and the Bqt4 subfamily is included in it and is poorly understood in filamentous fungi. In this study, we evaluated the role in growth and pathogenesis of the homologous of Bqt4, FspTF, in Fusarium sp. isolated from the ambrosia beetle Xylosandrus morigerus through the characterization of a CRISPR/Cas9 edited strain in Fsptf. The phenotypic analysis revealed that FT65-6, the edited strain, modified its mycelial growth and conidia production and exhibited affectation in mycelia and culture pigmentation and in the response to certain stress conditions. In addition, the plant infection process was compromised. Untargeted metabolomic and transcriptomic analysis, clearly showed that FspTF may regulate secondary metabolism, transmembrane transport, virulence and diverse metabolic pathways such as lipid metabolism, and signal transduction. These data highlight for the first time the biological relevance of an orthologue of Bqt4 in Fusarium sp. associated with an ambrosia beetle.This is a provisional file, not the final typeset article Ambrosia beetles are members of the wood-decaying ecosystem, are xylem-borers of dead and stressed trees that perform fungus farming as an ecological strategy, and carry spores of symbiotic fungi in specialized structures of their exoskeletons (the mycetangium). Once the insect is established in the plant host, the fungi colonize the drilled galleries and serve as the only source of food for both the adult beetle and the developing larvae (Six, 2012;Kirkendall et al., 2015;Huang et al., 2020; Dzurenko and Hulcr, 2022). The beetle-fungi associations are variable from the highly specific nutritional symbiosis to less specific association with other fungi acquired from the environment but which are established on the abdomen or external surfaces. Thus, fungal mycobiome is considered complex and include phytopathogens